Thermal properties and cold crystallization kinetics of deep eutectic solvents confined in nanopores. Issue 25 (22nd June 2021) - Lan, Xue; Wang, Xin; Du, Weihong; Mu, Tiancheng; Lan, Xiao Zheng
Abstract : Thermal properties, crystal structures and cold crystallization kinetics of deep eutectic solvents confined in nanopores alter significantly due to the size effect and interfacial interactions. Abstract : Herein, the phase behaviors of both bulk and confined deep eutectic solvents in controlled pore glasses were first investigated. Glass transition, cold crystallization and melting behaviors alter significantly in the nanopores due to the size effect and interfacial interactions. Kinetic analysis of the crystallization reveals increased effective activation energies and pre-exponential factors under nanoconfinement.